(untitled) (Comprehensive Journal of Science, 2025)
This study aimed explicitly and directly to examine the role of using electronic information systems in internal auditing activities at Libyan universities. The study was conducted through a field survey applied to Libyan universities, namely the University of Zawiya and the University of Sabratha. To achieve the study’s objectives, the researcher designed a questionnaire consisting of (24) items to measure the role of electronic information systems in internal auditing practices within the selected universities. A total of (14) questionnaires were distributed to internal auditors through personal interviews, all of which were fully completed and collected. The collected data were analyzed using the Statistical Package for Social Sciences (SPSS), employing both descriptive and inferential statistical methods. The study concluded with several key findings, most notably that the use of electronic systems significantly contributes to improving the performance of internal auditors by enhancing accuracy, increasing speed, and improving the quality of analysis and reporting. The study also presented several recommendations, the most important of which is the necessity of continuously developing and updating electronic accounting systems in line with the requirements of modern internal auditing practices.